Kur’an’da şefaat kavramı ve yaygın şefaat anlayışıyla karşılaştırılması - Yılmaz, Mehmet (My University, 2006)
sefaat, tevbe, magfiret, günah, vesile, ÖZET “Kur’an’da Sefaat Kavramı ve Yaygın Sefaat Anlayısıyla Karsılastırılması” İslâm öncesi din ve kültürlerde çesitli sekillerde var olan sefaat olgusu; Kur’ân’ın da önemle üzerinde durdugu konulardan biridir. Kur’ân’da sefaatin ortaya konulus sürecinde, öncelikle nüzul dönemi muhataplarının inanç dünyalarında önemli bir yer tutan yanlıs (çarpık) sefaat anlayısı reddedilmis, daha sonra Kur’ân’ın kendi üslubu içerisinde gerçek sefaat anlayısının temel ilkeleri ortaya konmustur. Kur’ân’da sefaatin hem varlıgına hem de yokluguna yorumlanabilecek âyetlerin yer almasından dolayı sefaat hakkında farklı görüsler ortaya çıkmıstır. Kur’ân’ın öngördügü sefaat anlayısına ulasmak için sefaatle ilgili âyetlerin nüzul sürecinin dikkate alınması ve bütüncül anlayısla degerlendirilmesi gerekir. İslâm düsünce tarihinde sefaati kabul eden ve reddeden anlayıslarının ortaya çıkmasında mezheplerin konuyu genel ilkeleri çerçevesinde degerlendirmeleri ve parçacı bir bakıs açısıyla ele almaları etkili olmustur. Sefaat konusunda geçmiste ortaya çıkan bu farklı anlayıslar, günümüz Müslümanlarının inanç dünyasına da yansımıstır. Yaptıgımız arastırmada, günümüzde de sefaatin varlıgını kabul eden ve reddeden görüslerin oldugu ortaya çıkmıstır. Bu farklı anlayısların ortaya çıkmasında Kur’ân’ın ifadelerinin dısında konu hakkında sıhhati tartısmalı rivayetlerin ön plana çıkarılması etkili olmustur. Ayrıca toplumun sefaat hakkında dogru ve yeterli bilgiye sahip olmadıgı da tespit edilmistir. Sonuç olarak; âyet ve hadislerden anlasıldıgı kadarıyla Allah’ın koydugu sınırlar ve ölçüler içerisinde, ahirette sefaat gerçeklesecektir. Allah’ın izni dısında hiç kimse sefaat edemeyecektir. Dolayısıyla sefaatin tek mercii Allah’tır. Sefaatin gerçeklesme sekli ise; Allah’ın af ve magfiret müjdesinin bazı seçkin kisiler aracılıgıyla, Allah’ın izin verdigi ve rızasını kazanmıs kullara ulastırılacagı bir “ödül töreni” ne benzetilebilir.

“ Intercession Concept in the Qur’an and its Comparison of Popular Understanding” Intercession phenomenon was existed in the Pre-Islamic era’s culture and religion in various ways, which is one of the important concepts that Qur’an reveals. In the process of revelation for the intercession in the Qur’an, firstly wrong (unacceptable) understanding of intercession, which was very important place for their followers’ belief during the time of revelation, was denied after that, basic principles of real understanding of intercession were manifested within the Qur’anic style. Because of the presence of some verses in the Qur’an to be commented either existence or the absence of the intercession different views were emerged. In order to reach to the understanding of intercession that the Qur’an anticipated, consideration the reason of revelation of those verses related to intercession and total assessment are required Evaluation of the concept by Islamic Sects has been effective within the framework of general principles and assessment with a narrow point of view in the emerging of belief rejecting and accepting the concept of intercession in the history of Islamic idea. Diverse views about intercession emergent in the past reflected upon today’s Moslem’ faith. This research showed the presence of both views rejecting and accepting the concept of intercession today. Controversial rumours about the subject were very effective in emerging the different understandings of views out of Qur’anic verses. Moreover, it was found that the society has not enough and right knowledge about intercession. Consequently, as far as understood from the Qur’an and the hadith there is no doubt that intercession will be accomplished in the hereafter but within the boundary and the standards that Allah lay down upon for all mankind. No one can perform intercession except Allah and those who are permitted by Allah. Therefore, the only authority for intercession is the Allah. The format of the intercession seems to be an “award ceremony” to convey the good news of forgiveness and mercy of Allah by means of distinct individual for those who gained permission and Allah’s consent.
Keywords: İslam Dini; Kelam; Kur’an-ı Kerim_Kelam